Penerapan Asas-Asas Hukum dalam Perjanjian Jasa Konstruksi: Suatu Kajian Normatif - Wiraantaka, Jaka Adiprasetya; Sami’an, S.; Hardjomuljadi, Sarwono (CV. Social Politic Genius (SIGn), 2024)
Construction service contracts, as crucial legal instruments in infrastructure development, require a strong foundation of civil law principles. This research aims to normatively examine the application of civil law principles in construction service contracts, integrating the perspectives of the Civil Code and Law Number 2 of 2017. This normative legal research employs statute, conceptual, and philosophical approaches, as well as teleological and sociological analyses. The research findings indicate that formal principles, such as freedom of contract, consensualism, good faith, privity, and fair competition, form the foundation for the validity of contracts. Meanwhile, substantive principles, such as pacta sunt servanda, reasonableness, custom, balance, equality, partnership, and deliberation to reach a consensus (musyawarah mufakat), determine the substance of a fair and sustainable contract. However, teleological and sociological analyses reveal complex dynamics in their application. Unequal bargaining power, standard clauses, discrimination, and short-term orientations hinder the optimal realization of these principles. Therefore, synergy among stakeholders is needed to increase legal awareness, strengthen regulations, enforce business ethics, and revitalize local wisdom values so that legal objectives can contribute to achieving state goals.